2007
DOI: 10.1029/2007gl029683
|View full text |Cite
|
Sign up to set email alerts
|

The Atlantic Meridional Mode and hurricane activity

Abstract: [1] Connections between the Atlantic Meridional Mode (AMM) and seasonal hurricane activity are investigated. The AMM, a dynamical ''mode'' of variability intrinsic to the tropical coupled ocean-atmosphere system, is strongly related to seasonal hurricane activity on both decadal and interannual time scales. The connection arises due to the AMM's relationship with a number of local climatic conditions that all cooperate in their influence on hurricane activity. Further analysis indicates that the Atlantic Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
215
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(243 citation statements)
references
References 29 publications
17
215
0
Order By: Relevance
“…Coupling of the warmed SSTs to the overlying atmosphere was also modest in ASO. However, aspects of the SST that were not well predicted were those that mattered more critically in this case: the North and tropical Atlantic SSTs (Goldenberg et al 2001;Vimont and Kossin 2007), including the main development region (Goldenberg and Shapiro 1996). These regions developed markedly stronger positive anomalies than had been observed in April and May or forecast for the forthcoming peak season months, and are believed to have been a major cause of the high 2004 Atlantic TC activity level.…”
Section: A Favorable and An Unfavorable Real-time Forecastmentioning
confidence: 74%
See 1 more Smart Citation
“…Coupling of the warmed SSTs to the overlying atmosphere was also modest in ASO. However, aspects of the SST that were not well predicted were those that mattered more critically in this case: the North and tropical Atlantic SSTs (Goldenberg et al 2001;Vimont and Kossin 2007), including the main development region (Goldenberg and Shapiro 1996). These regions developed markedly stronger positive anomalies than had been observed in April and May or forecast for the forthcoming peak season months, and are believed to have been a major cause of the high 2004 Atlantic TC activity level.…”
Section: A Favorable and An Unfavorable Real-time Forecastmentioning
confidence: 74%
“…For example, Fig. 7 shows the correlation field for SST in June versus Atlantic NTC during the ASO peak season, indicating the well-known inverse relationship with warm ENSO, and positive association with SSTs in the North Atlantic, associated with the Atlantic meridional mode (Vimont and Kossin 2007) and the Atlantic multidecadal oscillation (Goldenberg et al 2001). When September SST is used, simultaneous with the Atlantic TC activity, these same two key regions remain important, but even stronger correlations appear for SST in the main development region (Goldenberg and Shapiro 1996).…”
Section: Comparison With Simple Statistical Predictionsmentioning
confidence: 93%
“…1939 1940 1942 1941 1951 1944 1943 1957 1949 1945-1948 1963 1954 -1956 1950 1965 1964 1952 -1953 1969 1967 1958 -1962 1972 1970 -1971 1966 1976 1973 -1975 1968 1982 1988 1977 -1981 1986 -1987 1998 -1999 1983 -1985 1991 2007 1989 -1990 1997 1992 -1996 2002 2000 -2001 2006 2003-2005 2009 2008 Landsea (1993), Goldenberg and Shapiro (1996), Gray et al (1997), and Landsea et al (1999) have demonstrated that hurricane activity is tied to changes in the long-term pressure patterns in the Atlantic Ocean basin (e.g., the North Atlantic Oscillation, or NAO). Deser et al (2004) also demonstrate that sea level pressure and other background variables (e.g., wind shear) have displayed interdecadal variations, and Vimont and Kossin (2007) correlate these to Atlantic tropical cyclone activity. LJ00 and Lupo et al (2008) found that the influence of the PDO was manifested by changes in the ENSO-related variability, specifically, that there was little or no ENSO related variability during PDO2, and significantly fewer and less (more and more) intense hurricanes during EN (LN) years during PDO1.…”
Section: El Niño and Pacific Decadal Oscillation Definitionsmentioning
confidence: 99%
“…Regions with the warmest SSTs also are on average those regions with the lowest observed and simulated wind shear values. Research by Kossin and Vimont [2007] and Vimont and Kossin [2007] suggests that these covarying relationships among SST and other environmental variables (e.g., wind shear, relative humidity, static stability) modulate North Atlantic TC activity. Despite capturing the observed correlation between wind shear and SST, the models still fail to simulate stronger TCs in those environments that are more favorable (at least in terms of shear and SST) for intense TCs.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%